Association Between Korean-Style Balanced Diet and Risk of Abdominal Obesity in Korean Adults: An Analysis Using KNHANES-VI (2013–2016) - Yang, Hye Jeong; Kim, Min Jung; Hur, Haeng Jeon; Lee, Byoung Kook; Kim, Myung-Sunny; Park, Sunmin (Frontiers in Nutrition, 2022)
Abdominal obesity is a critical factor for metabolic diseases, and specific eating patterns such as the Mediterranean diet help prevent metabolic diseases. This study aimed to investigate the association between the modified Korean health eating index (MKHEI), including a Korean-balanced diet, and abdominal-obesity risk according to genders in adults aged 20–64 years (4,886 males and 7,431 females), using the Korea National Health and Nutrition Examination Survey VI (2013–2016). Adjusted means and 95% confidence intervals of MKHEI scores and nutrient intake estimated using the 24-h recall method were calculated according to abdominal obesity (i.e., waist circumference ≥90 cm for men and ≥85 cm for women) after adjusting for age, residence area, region, education, income, drinking status, smoking status, marital status, and exercise. Adjusted odds ratios (ORs) for abdominal obesity were measured according to MKHEI tertiles using logistic regression analysis while controlling for covariates. Individuals aged >50 years, married, below high school, lower-income, heavy alcohol drinkers, past and current smokers, and males living in the southern areas had a higher risk of abdominal obesity. In both sexes, the scores of all MKHEI components were lower in the abdominal obesity group (n=2895) than in the control group (n=9422) in both sexes. Further, the scores of fruits with and without fruit juice were lower in the abdominal obesity group. Meanwhile, the scores of beans, including fermented beans, were lower in the abdominal obesity group only in females but not in males. Further, the scores of fast foods were higher in the abdominal obesity group than in the control group only in females. After adjusting for covariates, the adjusted OR for abdominal obesity was inversely associated with Korean balanced diet (KBD) related to KHEI scores. Unlike MKHEI of KBD, that Western-style diet was not associated with abdominal obesity in either sex. In conclusion, KBD can lower the risk of abdominal obesity in females and should thus be recommended to prevent abdominal obesity.